Flurbiprofen Ameliorates Glucose Deprivation-Induced Leptin Resistance - Hosoi, Toru; Suyama, Yuka; Kayano, Takaaki; Ozawa, Koichiro (Frontiers in Pharmacology, 2016)
Leptin resistance is one of the mechanisms involved in the pathophysiology of obesity. The present study showed that glucose deprivation inhibited leptin-induced phosphorylation of signal transducer and activator of transcription 3 (STAT3) and signal transducer and activator of transcription 5 (STAT5) in neuronal cells. Flurbiprofen reversed glucose deprivation-mediated attenuation of STAT3, but not STAT5 activation, in leptin-treated cells. Glucose deprivation increased C/EBP-homologous protein (CHOP) and glucose regulated protein 78 (GRP78) induction, indicating the activation of unfolded protein responses (UPR). Flurbiprofen did not affect the glucose deprivation-induced activation of UPR, but did attenuate the glucose deprivation-mediated induction of AMP-activated protein kinase (AMPK) phosphorylation. Flurbiprofen may ameliorate glucose deprivation-induced leptin resistance in neuronal cells.